2019
DOI: 10.1021/acs.macromol.9b00464
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity Scaling and Free Volume in Plasticized Polylactide

Abstract: The experimental evidence of the increase of activation energy associated with the super Arrhenius behavior governing amorphous polylactide by free volume variations has been obtained through a combination of calorimetric, dielectric, and positron annihilation lifetime measurements. The amount of free volume in polylactide was controlled by the amount of acetyltributylcitrate plasticizer in the composition. Plasticization is shown to decrease both the fragility index and the scale of cooperative motions at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“…It was observed [24,25] by modulated temperature differential scanning calorimetry (MTÀ DSC) and dielectric relaxation spectroscopy (DRS) that the ATBC molecules decrease the kinetic fragility index, and that this result coincides with the decrease of the size of CRR [25]. Recently [26], we have shown that the variations of the CRR size in plasticized PLA are consistent with the variations of the free volume obtained experimentally from positron annihilation lifetime spectroscopy (PALS).…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…It was observed [24,25] by modulated temperature differential scanning calorimetry (MTÀ DSC) and dielectric relaxation spectroscopy (DRS) that the ATBC molecules decrease the kinetic fragility index, and that this result coincides with the decrease of the size of CRR [25]. Recently [26], we have shown that the variations of the CRR size in plasticized PLA are consistent with the variations of the free volume obtained experimentally from positron annihilation lifetime spectroscopy (PALS).…”
Section: Introductionsupporting
confidence: 82%
“…Fig. 6 shows PALS results as a function of temperature that have been obtained during glass transition and cold crystallization of initially amorphous PLAs [26]. In the glassy state, f v is nearly constant and increases from 1.6 for neat PLA to 1.8% for PLA_10.…”
Section: Free Volume and Glass Transition Cooperative Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations